On the origin of C₆₀ fullerene solubility in aqueous solution - Prylutskyy, Yu I (Langmuir : the ACS journal of surfaces and colloids, 2014)
In this work, we report that the surface hydroxylation of C60 molecules is the most likely mechanism for pristine C60 fullerenes/C60 fullerene aggregate stabilization in water, being independent of the method of C60 fullerene aqueous solution preparation